The optimizing of land facilities at port of Kolaka in Southeast Sulawesi Province - Chaidirrozi Chaidirrozi; Febriansyah Febriansyah; Zazkia Ramadhani (Puslitbang Transportasi Antarmoda-Kementerian Perhubungan Republik Indonesia, 2020)
To improve ferry operation services, adequate port facilities are needed in order to create safety, security, and comfort for passengers, vehicles and the ship itself. The land facilities at the port which have great importance are passengers’ waiting rooms, gangways, and weighbridge.This study is aimed to review the passenger’ waiting rooms, gangways, and weighbridge at Port of Kolaka which is located in the Province of Southeast Sulawesi. Data were collected using observation. The researchers also used secondary data to support the findings. To analyze the data, the researcher compared the existing conditions with the ideal conditions based on two government regulations (1) the Decree of the Minister of Transportation No.KM 52 Year 2004 concerning the Management of the Inland Ports; (2) the Decree of the Director General of Land Transportation No. SK.2681 / AP.005 / DRJD / 2006 concerning the Operation of the Inland Ports.The result of this study showed that the facilities at the Inland Port of Kolaka are not used optimally and accordingly which at some points can endanger the safety of the passengers. Therefore, improvements are needed to optimize the function of the facilities.